Theoretical and Experi-Mental Study to Investigate the Acoustic Absorption Performance of Natural Luf-Fa Fibers - Lamyaa Abd ALRahman Jawad, Tawfeeq Wasmi M. Salih (International Journal of Advanced Science and Technology, 2020)
This research focuses on the acoustical absorption performance of a natural porous material which is Luffa. In addition, Luffa grows up rapidly and profusely, thus it would be a contribution to green technology. The study has been done theoretically and experimentally using composites of Luffa fibers (LF) with latex. Theoretically, two approaches were used known as Delany-Bazley and Biot-Allard, to calculate the values of acoustic absorption coefficient (AAC) at frequencies range from 100 Hz to 5000 Hz. The experimental work included preparing of LF, manufacturing the specimens and measuring the AAC using an impedance tube instrument for selected samples of 30, 40 and 50 mm thickness. Results show that AAC value is increased by increasing the thickness and bulk density for certain ranges. Where in low frequencies range between (100 Hz to 1.2 kHz); each 10 mm layer added improves the AAC value by 10-15 %. The comparison between the theoretical and experimental values shows slight differences by (±25%) due to some approximations in the assumed parameters, as well as some experimental regards. For example, the peak values of AAC, for frequencies range between (1.2 kHz to 5 kHz), were swinging between (0.8-1) theoretically and between (0.6-0.9) experimentally.